2007
DOI: 10.1177/0363546506294678
|View full text |Cite
|
Sign up to set email alerts
|

Discoid Meniscus

Abstract: This difference may contribute to the vulnerability of the discoid meniscus to tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(57 citation statements)
references
References 12 publications
1
54
0
2
Order By: Relevance
“…The histology and ultrastructure of discoid meniscus is different from that of normal meniscus. The discoid meniscus is characterized by decreased collagen fibers and loss of normal collagen orientation, and intrameniscal mucoid degeneration is also common9,22). Papadopoulos et al23) documented significant disorganization of the circular collagen network and a heterogeneous course of the circumferentially arranged collagen fibers in discoid meniscus structure.…”
Section: Embryology and Anatomymentioning
confidence: 99%
“…The histology and ultrastructure of discoid meniscus is different from that of normal meniscus. The discoid meniscus is characterized by decreased collagen fibers and loss of normal collagen orientation, and intrameniscal mucoid degeneration is also common9,22). Papadopoulos et al23) documented significant disorganization of the circular collagen network and a heterogeneous course of the circumferentially arranged collagen fibers in discoid meniscus structure.…”
Section: Embryology and Anatomymentioning
confidence: 99%
“…Microscopic tissue examinations through human embryos knee joint revealed the meniscus and cruciate ligament develops directly from an intermediate mesodermal blastoma, which has the shape of a thick plate in the early embryonic period. 12 15 16 According to this present case, medial meniscus and anterior cruciate ligament may be differentiated from same embryonic tissue and it may provide evidence of congenital developmental assumption of discoid meniscus. Our patient had a history of pain with extension block in accordance with standard surgical treatment indicated in symptomatic patients with persistent pain or recurrent locking or catching like mechanical block.…”
Section: Discussionmentioning
confidence: 52%
“… 11 Atay et al . 12 in their study have reported that decreased amount of collagen fibers with heterogenous configuration under the electron microscopic findings may be the causative factor of vulnerability of the discoid meniscus. Others may include relatively weak attachments to the joint capsule of the posterior horn, insufficient vascular supply and thickness of discoid shape.…”
Section: Discussionmentioning
confidence: 89%
“…Unlike normal menisci, discoid menisci cannot control the coordination of the tibiofemoral joint, absorb shock, or reduce the mechanical pressure on articular cartilage, thus they quickly become worn and are torn easily, particularly when injured (14). Atay et al (15) revealed that the ultrastructure of discoid lateral menisci significantly differs from that of normal menisci. The collagen fibrils in discoid menisci are decreased in number and misaligned, both of which contribute to an increased incidence of tears.…”
Section: Discussionmentioning
confidence: 99%